Transition of care of adolescents with rheumatic diseases in Saudi Arabia, current practice and obstacles - Khouloud Bakheet; Emtenan Basahl; Waleed Hafiz; Reima Bakry; Mohammed Nashawi (Elsevier, 2024)
Background: The importance of transition of care for adolescents with rheumatological illnesses from pediatric to adult rheumatology is increasing as the childhood rheumatologic diseases continue to adulthood. Despite that, transition practice in Saudi Arabia is not yet well-developed. Objectives: This study aims to evaluate the current transition of care practice for adolescents with rheumatological diseases to the adult healthcare facilities and the obstacles in achieving the best transition of care in Saudi Arabia. Setting and methods: This is a non-interventional cross-sectional study conducted using an online survey that was distributed to pediatric and adult rheumatologists in Saudi Arabia. Google forms and Microsoft Excel 2016 were used for data entry and analysis. Descriptive statistics, frequencies and percentages were performed for categorical variables. Results: A total number of 60 rheumatologists (27 pediatric and 33 adult) participated in the survey. Fifty-six (94%) of the participants do not follow any standardized programs for transition of care. All participants agreed on the need for a defined protocol for transition of care. The major barriers for successful transition of care were lack of protocols (63%), lack of healthcare providers (56%), and lack of well-developed systems that makes it difficult to access patient's electronic health records (55%). Conclusion: A well-structured protocol for transition of care of adolescents with rheumatologic illnesses from pediatric to adult rheumatology in Saudi Arabia is still an unmet need. Efforts should be directed towards improving the practice of transition of care by establishing this protocol, enhancing the connectivity between pediatric and adult healthcare facilities, and encouraging pediatric and adult rheumatologists to adapt the transition of care protocol in their daily clinical practice.